"OH! LET THE BOYS FIGHT, IT'S IN THEIR NATURE” - A STUDY ON GENDER STEREOTYPES IN REGARDS TO PUNISHMENT MEASURES - Sophie Duteil Deyries (Holos, 2016)
As demonstrated by a number of studies on the construction of gender roles, school staffs continue to discriminate, in a number of ways, between girls and boys. The male pupils and the female pupils are not considered or handled in the same way, and punishment is an important part of this discriminatory system. The study aims to show, through the example of punishment, how girls and boys are subjected to gender-specific conditioning in a high-school of the region of Montpellier (South of France). By basing itself both on quantitative methodologies (questionnaires, study of archives and of the use of certain "words" [disciplinary remarks] in the pupil report cards) and qualitative ones (discussion with the teachers), the study at hand gives cause for statistics and thematic analysis, demonstrating how the behavior of adults and pupils is both discriminating and discriminated against. Several hypotheses allow one to grasp what takes place when a punishment is handed out to a pupil and what it furthers in the child, the adult, and their peers. This study was conducted in France, as final thesis of a Master’s degree.